Effect of Different Levels of Egg Shell in Diet on the Production Performance, Egg Quality and Heavy Metal Contents in Laying Hens - Hassan , M.R.; Naushinara, A.S.; Sultana, S.; Rabbani, M.A.G.; Faruque, S.; Shammi, M.; Rahman, M.M.; Khabiruddin, M.; Sultana, N. (International Journal of Poultry Science, 2022)
Background and Objective: In Bangladesh, huge amount of eggshell-waste is produced every day. Most of them are discarded into the environment. However, it can be a resource upon proper management. As eggshell contains around 40% calcium which is beneficial as poultry feed. Therefore, the present experiment was conducted to convert eggshell-waste as a dietary source of laying hen. Materials and Methods: In this experiment, a total of 50 kg of eggshell was collected from farm and local food vendors. At 30 weeks of age, a total of 100 laying hens were randomly selected and were divided into 5 groups with 4 replications. The treatments were: T0: Control group-100% limestone, T1: 75% limestone and 25% eggshell based-feed, T2: 50% limestone and 50% eggshell based-feed, T3: 25% limestone and 75% eggshell based-feed and T4: 100% eggshell-feed. The hens were fed with 120 g/hen/day and water was provided ad-libitum during the experiment. The standard management system was followed. Results: A significantly higher egg weight and eggshell weight was found by feeding of 100% eggshell based-feed treatment (p